Volatility Transmission and Spillovers among Gold, Bonds and Stocks: An Empirical Evidence from Turkey - Gencer, Gaye; Musoglu, Zafer (International Journal of Economics and Financial Issues, 2014)
This paper examines the volatility transmission mechanisms bivariately, between gold prices and alternatively, Turkish stock market and government bond indices. We employ the BEKK-GARCH model for evaluating the volatility linkages, as a robust technique. We investigate the period between June 2006 and November 2013, which infact, is a highly volatile period in the world economy, marked by the 2008 crisis. Our results confirm a bi-directional shock and volatility transmission between gold prices and Turkish stock market, whereas we document a uni-directional transmission from gold asset to Turkish government bonds. Based upon our BEKK-GARCH model corollaries, we design two hedged portfolios consisting of gold/stocks and gold/bonds. The optimal portfolio weights and hedge ratios are computed to signify that adding a portion of gold in bond and stock portfolios, enhances investment efficiency. Our empirical findings depict gold as a unique asset to reduce the portfolio risk especially in times of adverse market conditions in Turkey. Thus, our study conveys significant implications to international investors and portfolio managers in portfolio diversification and risk management. Keywords: Gold; Stocks; Bonds; Portfolio Diversification JEL Classifications: G01; G11; G15